Tinker, Taper, QE, Bye? The Effect of Quantitative Easing on Financial Flows to Developing Countries - Lim, Jamus Jerome; Mohapatra, Sanket; Stocker, Marc (World Bank, Washington, DC, 2014)
This paper examines gross financial inflows to developing countries between 2000 and 2013, with a particular focus on the potential effects of quantitative easing policies in the United States and other high-income countries. The paper finds evidence for potential transmission of quantitative easing along observable liquidity, portfolio balancing, and confidence channels. Moreover, quantitative easing had an additional effect over and above these observable channels, which the paper argues cannot be attributed to either market expectations or changes in the structural relationships between inflows and observable fundamentals. The baseline estimates place the lower bound of the effect of quantitative easing at around 5 percent of gross inflows (for the average developing economy), which suggests that of the 62 percent increase in inflows during 2009-13 related to changing global monetary conditions, at least 13 percent of this was attributable to quantitative easing. The paper also finds evidence of heterogeneity among different types of flows; portfolio (especially bond) flows tend to be more sensitive than foreign direct investment to our measured effects from quantitative easing. Finally, the paper performs simulations that explore the potential effects of the withdrawal of quantitative easing on financial flows to developing countries.